Saliva Microbiome Changes in Patients With Periodontitis With and Without Chronic Obstructive Pulmonary Disease - Lin, Mei; Li, Xuefen; Wang, Jitian; Cheng, Cheng; Zhang, Tianyi; Han, Xiaozhe; Song, Yiqing; Wang, Zuomin; Wang, Songlin (Frontiers in Cellular and Infection Microbiology, 2020)
ABSTRACT Objective: The oral microbiota plays a key part in the initial colonization by pathogens and chronic inflammatory reaction of the host. We measured variations in the salivary microbiota, and evaluated their potential associations with periodontitis and chronic obstructive pulmonary disease (COPD). Methods: We investigated the salivary microbiota of patients with COPD and periodontitis (n = 21) compared with that in patients with periodontitis alone (n = 36) and with healthy controls (HCs; n = 14), using pyrosequencing of polymerase chain reaction-amplified 16s rRNA genes. Results: Bacterial richness and diversity were significantly higher in patients suffering from COPD, and the bacterial family Lachnospiraceae was observed frequently only among patients with COPD and periodontitis. Veillonella, Rothia, Actinomyces, and Fusobacterium were the core bacterial genera that showed significant differences among patients with coincident COPD and periodontitis, patients with periodontitis alone, and HCs (p < 0.05). Veillonella, Rothia, and Actinomyces were observed much more frequently in patients with COPD and periodontitis, compared with that in HCs. All tested populations were divided into subgroups based on sex, smoking or periodontitis index. In the subgroup with a bleeding index >2, Rothia was significantly different in periodontitis with and without COPD groups compared with HCs. In the subgroup with a plaque index >2.5, Rothia and Veillonella showed significant differences in periodontitis with and without COPD groups compared with HCs. Conclusion: Variations in salivary microbiota may be associated with COPD and periodontitis. Significant differences in levels of certain residents in the salivary microbiota may help to identify potential risk factors that contribute to COPD pathogenesis.